Inventory Of Spermatophyta Of Tanjung Setia Krui Beach Vegetation As A Source Of Biological Learning - Suharno Zen; Rinta Apriliani (PENBIOS: JURNAL PENDIDIKAN BIOLOGI DAN SAINS, 2020)
The objectives of the study were: 1) to determine the types of high-level plants that make up the coastal vegetation in Tanjung Setia Krui Beach, 2) to determine the diversity and dominance of high-level plants at Tanjung Setia Krui Beach, 3) to determine the results of research on the inventory of high-level vegetation on Tanjung Setia Krui Beach to be used as a source of learning biology in high school in the form of an encyclopedia. This research method is sampling using purposive sampling method with a plots. The higher plants that were found were then identified in that place. The results showed that 20 species from 12 families. Family Hydrocaritaceae, Family Potamogetonaceae, Family Convolvulaceae, Family Poaceae, Family Arecaceae, Family Pandanaceae, Family Combretaceae, Family Asteraceae, Family Malvaceae, Family Portulaceae, Family Leguminosae, Family Lecythidaceae. The three stations have a value of 1≤H'≤3 which means that they show moderate diversity. The conclusion of this study is that the inventory of high-level plants that makes up coastal vegetation at Tanjung Setia Krui Beach was used as a learning resources for high school biology class X on Biodiversity material in the form of an Encyclopedia.